Familial median canaliform dystrophy of heller affecting multiple nails: a rare clinical entity - Jain, Chandni; Shaafie, Harris Ishtiyaq; Farooque, Mustaqueem; Wahab, Zarin (International Journal of Research in Dermatology, 2021)
Median canaliform dystrophy (MCD); first described by Heller in 1928 is characterized by a midline or paramedian split in the nail plate. Mostly idiopathic, some identifiable causes include habitual picking of the nails, oral isotretinoin use and positive family history. The familial occurrence of MCD has rarely been described. Till date, no therapy has proven to be consistently successful in effectively managing the condition. Commonly utilized treatments have been intralesional triamcinolone acetonide injections into the dystrophic nail, topical 0.1% tacrolimus ointment and topical tazarotene 0.05% ointment. Despite available treatment options, the condition has a tendency to recur. Here; we report a case of a 14‑year‑old male presenting with familial MCD affecting multiple finger and toe nails.